Chemical characterisation of small substructures in the local stellar halo - Dodd, Emma; Matsuno, Tadafumi; Helmi, Amina; Balbinot, Eduardo; Callingham, Thomas M.; Starkenburg, Else; Woudenberg, Hanneke C.; Ruiz-Lara, Tomás (Astronomy and astrophysics, 2025)
Context. The local stellar halo of the Milky Way is known to contain the debris from accreted dwarf galaxies and globular clusters in the form of stellar streams and over-densities in the space of orbital properties (e.g. integrals of motion). Aims. While several over-densities have been uncovered and characterised dynamically using Gaia data, their nature is not always clear. Especially for a complete understanding of the smaller halo substructures, the kinematic information from Gaia needs to be coupled with chemical information. Methods. In this work, we combine Gaia data with targeted high-resolution UVES spectroscopy of five small substructures that were recently discovered in the local halo, namely ED-2, -3, -4, -5, and -6 (the ED streams). We present the chemical abundances measured from our newly obtained UVES spectra (20 stars) and from archival UVES spectra (nine stars). We compared these with homogeneously derived abundances from archive spectra of 12 Gaia Enceladus (GE) stars. Results. The chemical abundances of all five substructures suggest that they are of accreted origin, except for two stars that present a high [α/Fe] at high [Fe/H] more in line with an in situ origin. All but ED-2 present a significant spread in [Fe/H] suggestive of a dwarf galaxy origin. ED-3 and ED-4 tend to exhibit a lower [α/Fe] compared to GE stars. As for ED-5 and ED-6, they are consistent with the GE chemical track and could be high-energy tails of GE that were lost earlier in the accretion process. We present new elemental abundances for five ED-2 stars, including more elements for the Gaia BH3 companion star. Our findings are in line with the picture that ED-2 is a disrupted ancient star cluster.
Online veröffentlicht: 14. August 2025
Gesehen am 14.01.2026